Perjuangan yang belum Selesai: Bahagian Hal Ehwal Pelajar dan Alumni UMT Mendepani Cabaran COVID-19 - Zakariya, Hafiz (Universiti Malaysia Terengganu Press, 2021)
This study is a sequel to UMT Prihatin. This book focuses on major developments at UMT from 1 August 2020 to 30 June 2021. It describes the major events and challenges faced by the Office of Student Affairs & Alumni during the stated period. It details out HEPA's activities to look after students' welfare during this period. In addition, it discusses UMT's involvement with the community.